Effectiveness of the role-playing shaftel (RPS) model for enhancing social skills in primary school physical education - Budiman; Hidayat, Yudi; Rusmana, Ruslan; Sutiswo; Febriani, Angelina Chyntia (Edu Sportivo: Indonesian Journal of Physical Education, 2025)
Background: Social skills are essential for primary school students, yet few studies have examined the effectiveness of the Shaftel Role-Playing (RPS) model in Physical Education (PE), particularly in Indonesia. Objectives: This study aimed to examine and evaluate the effect of the Shaftel Role-Playing (RPS) model on the development of students’ social skills in Physical Education learning. Methods:  A one-group pretest–posttest design was implemented with 30 sixth-grade students selected through simple random sampling. The RPS intervention was delivered across 12 sessions (70 minutes each). Finding/Results: The analysis revealed a statistically significant improvement in students’ social skills following the implementation of the RPS model (Sig. = 0.013). The intervention demonstrated a medium effect size (Cohen’s d = 0.49), indicating that the model produced a meaningful and practically relevant impact on students’ social skill development. Conclusion: The findings confirm that the Shaftel Role-Playing (RPS) model significantly enhances elementary students’ social skills within Physical Education learning. This result highlights the model’s potential as an effective pedagogical strategy for fostering social competence in school-based contexts, although future studies using controlled designs are recommended to further validate these outcomes.